New clathrates of Rb7.50(1)Tl0.50(1)Ge46 and K7.62(1)Tl0.38(1)Ge45.34(3). Issue 79 (9th August 2016) - Zhang, Hui; Mu, Gang; Huang, Fuqiang; Xie, Xiaoming
Abstract : Rb7.50(1) Tl0.50(1) Ge46 and K7.62(1) Tl0.38(1) Ge45.34(3) are synthesized and characterized. Abstract : New Tl type-I clathrates of K7.62(1) Tl0.38(1) Ge45.34(3) and Rb7.50(1) Tl0.50(1) Ge46 were synthesized via solid-state reaction. Rb7.50(1) Tl0.50(1) Ge46 and K7.62(1) Tl0.38(1) Ge45.34(3) were found to crystallize in space groups Pm 3̄ n and Ia 3̄ d with lattice parameters of a = 10.81559(7) Å and a = 21.4290(2) Å, respectively. Theoretical calculations indicated metallic features based on the calculation models of Rb7 Tl1 Ge46 and K7 Tl1 Ge46 in the space group of Pm 3̄. The densities of states at the Fermi level were predominantly determined by the Ge s and Ge p orbitals of Rb7 Tl1 Ge46 and K7 Tl1 Ge46 .